PENGARUH EKSPEKTASI PENDAPATAN, PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA DI PERGURUAN TINGGI NEGERI DI KOTA MEDAN - RUDY .; FINESTASYA SUTAN (LP2MTBM MAKARIOZ, 2020)
State Universities in Medan City have a total of 117,105 students in the 2018-2020 period, of which only about 10% are interested in becoming entrepreneurs. This is due to the income expectations estimated by some state students in Medan City are still not in line with their expectations, so they are not too enthusiastic about participating in the entrepreneurship education that has been taught by lecturers on their campuses, as a result they do not have the excessive motvation to become an entrepreneur, so they still think that after graduation they will find a job to make ends meet instead of wanting to become entrepreneurs. This research aims to find out how the influence of income expectations thought by state university students in Medan city, entrepreneurship education taken by students at State University in Medan City and the motivation for student entrepreneurship at State University in Medan City on the interest of State University students to become entrepreneurs. The total population in this study amounted to 117,105 students at the State University in Medan City, where the sampling technique used the accidental sampling technique with a total sample of 44 people calculated with the slovin formula.TThe results of the study can be concluded that simultaneously the variable income expectations thought by state university students in Medan City, entrepreneurship education taken by students at State University in Medan City and student entrepreneurial motivation at State University in Medan City have a positive effect on the variables of interest of State University students to become entrepreneurs, while partially only the variables of entrepreneurship education taken by students at State Universities in Medan City and student entrepreneurial motivation at State Universities in Medan City have a positive effect on the variables of interest of State University students to become entrepreneurs.